1983
DOI: 10.1136/gut.24.12.1169
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency in Crohn's disease.

Abstract: SUMMARY Fifty two patients with Crohn's disease (31 outpatients and 21 inpatients) were investigated for evidence of vitamin A deficiency. Eleven (21%) had low plasma retinol concentrations (<1.2 umol/l (34.3 ,ug%)). Five of these were outpatients and plasma retinol was only slightly reduced (>1.0 ,umoWl (28.6%)). All outpatients weighed 80% or-more of ideal, and were considered at low risk of developing vitamin A deficiency. In contrast, of the six inpatients with low plasma retinol concentration, five had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
2
12
1
2
Order By: Relevance
“…These findings confirmed earlier results of others for patients with Crohn's disease (Main, 1983;Schoelmerich, 1985). Furthermore, low serum retinol levels were found in patients with chronic pancreatitis or cholecystitis and in those with acute febrile illnesses (unpublished data).…”
Section: Discussionsupporting
confidence: 82%
“…These findings confirmed earlier results of others for patients with Crohn's disease (Main, 1983;Schoelmerich, 1985). Furthermore, low serum retinol levels were found in patients with chronic pancreatitis or cholecystitis and in those with acute febrile illnesses (unpublished data).…”
Section: Discussionsupporting
confidence: 82%
“…An ele vated fecal fat excretion was found in about half the Crohn's patients by Russell et al [8] and Main et al [6] as well as in the present study. Low serum carotene levels are often considered a useful and easily measured in dicator of fat malabsorption.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, the present study found normal serum retinol levels in all 137 outpa tients with CD over a 6-month period, al though low serum carotene values were ob served in 20-25% of these patients. A differ ence in retinol-binding protein levels, as a result of different protein status, may par tially account for the discrepancy in the prevalence of low serum retinol values be tween the present study and the study by Main et al [6]. Protein depletion was preva lent in the study by Main et al [6] but not in the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations